ANALISIS PENGAKUAN PENDAPATAN PADA CV. INTIMA SUKMANA PERDANA DI SAMARINDA - Pratiwi, Riczky Anantia (EKONOMIA, 2012)
The purpose of this study to know the suitability of the recognition of revenue recognized by the firm CV.Intima Sukmana Perdana in Samarinda in accordance with Financial Accounting Standards Entities Without Accountability( SAK ETAP) On construction contracts.Based on the results of the analysis and discussion CV. Intima Sukmana Perdana in Samarinda in carrying out theÂ Project Development District of the city Multipurpose Building construction contracts using the percentage completion method with a system of fixed price contracts. The calculation of revenue recognition in 2010 by CV. Intima Sukmana Perdana in Samarinda is Rp. 607.493.800,00 while according to the Financial Accounting Standards Entities Without Accountability (SAK ETAP) On construction contracts amounting to Rp. 804.750.357,60 resulting in a difference of Rp.197.105.257,60 Calculation of the recognition of receivables in 2010 by CV.Intima Sukmana Perdana in Samarinda is Rp. 82.838.700,00 whereas according to the Financial Accounting Standards Entities Without Accountability (SAK ETAP) On construction contracts amounting to Rp. 279.943.957,60 resulting in a difference of Rp. 197.105.25,60.The difference occurs because the percentage of completion method is applied by the CV. Intima Sukmana Perdana in Samarinda not correspond to percentage of completion method according to the Financial Accounting Entities Without Accountability (SAK ETAP) On the construction of his income, but by using a physical settlement has been completed.Based on the above conclusion hence that the recognition of revenue over alleged construction contract made by CV.Intima Sukmana Perdana in Samarinda not in accordance with Financial Accounting Entities Without Accountability (SAK ETAP) On the construction contract that is acceptable in calculating the revenue recognition.